2009
DOI: 10.2106/jbjs.h.00888
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Mapping of Meniscus and Cartilage Lesions Associated with Anterior Cruciate Ligament Injuries

Abstract: Increased age, male sex, and increased surgical delay all increase the frequency and severity of injuries of the meniscus and/or articular cartilage after an anterior cruciate ligament tear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
117
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(128 citation statements)
references
References 15 publications
10
117
0
Order By: Relevance
“…With each episode of giving way, meniscal tears can become more complex and less amenable to repair [8]. Studies in adult patients [7,8,24,39] and in pediatric patients [12,28,32] have shown an increased incidence of medial meniscal tears with delayed ACL reconstruction. Although the treatment of ACL tears in skeletally immature patients remains controversial [33], the risk of physeal injury and resulting growth disturbance from ACL repair to a patient with open physes is now thought to be small [15,22], and many centers (including our institution) opt for prompt reconstruction before skeletal maturity [9,16,20,25,31,34,40].…”
Section: Introductionmentioning
confidence: 99%
“…With each episode of giving way, meniscal tears can become more complex and less amenable to repair [8]. Studies in adult patients [7,8,24,39] and in pediatric patients [12,28,32] have shown an increased incidence of medial meniscal tears with delayed ACL reconstruction. Although the treatment of ACL tears in skeletally immature patients remains controversial [33], the risk of physeal injury and resulting growth disturbance from ACL repair to a patient with open physes is now thought to be small [15,22], and many centers (including our institution) opt for prompt reconstruction before skeletal maturity [9,16,20,25,31,34,40].…”
Section: Introductionmentioning
confidence: 99%
“…An ACL-deficient knee with a lateral meniscus lesion and a subsequent cartilage lesion on the lateral femoral condyle should be stabilised [11] and the lost meniscus tissue should be substituted. In each of the named examples cartilage repair is then nothing else than the topping on a tasty ice-cream.…”
mentioning
confidence: 99%
“…As previously discussed, both meniscal injury and direct articular cartilage trauma are linked to long-term cartilage damage following a knee injury and are predictive of long term tibiofemoral and patellofemoral osteoarthritis 48 . Given that isolated rupture of the ACL is relatively rare, and the majority of ACL ruptures are accompanied by meniscal and chondral damage, the overall rate of osteoarthritis following an injury resulting in an ACL rupture is likely to be closer to the quoted 'combined injury' rate than that reported for 'isolated injuries' 19,20,34 .…”
Section: How Strong Is the Link?mentioning
confidence: 94%
“…Damage to the menisci is observed in approximately 65-75% of ACL-ruptured knees during arthroscopy 19,34 . Traumatic longitudinal tears in the posterior and middle one-third of the medial menisci account for the majority of lesions, although damage to the posterior-middle portion of the lateral meniscus is also relatively common 20 ( Figure 2).…”
Section: Meniscal Injurymentioning
confidence: 99%
See 1 more Smart Citation